UI/UX Development Based On Design Thinking For Drug Swallowing Supervisors Of Pulmonary Tuberculosis Patients - Felix; Adriansyah, R.A. Fattah (Bahasa Indonesia, 2025)
Indonesia wants to achieve the WHO 2025 tuberculosis eradication strategy with a target incidence of less than 55 cases per 100,000 people. The Ministry of Health recorded the highest number of cases ever in 2024 with the number of cases reaching 1,060,000. Tuberculosis, which generally attacks the lungs, is expected to kill 40 million people in the world by 2050. Without intervention from various fields, this TB outbreak will have a terrible impact on the world's population, especially India and Indonesia, which occupy the 2 countries with the highest number of TB cases. The purpose of this study is to produce an analysis and design of an application that involves a drug swallowing supervisor (DSS) so that it can provide better control in order to increase the cure rate of pulmonary TB. In addition to supervisors, stakeholders involved can be patients, families, doctors, clinics, health offices, and the health ministry. Like Covid control, which is considered successful with the PeduliLindungi application which has now changed to SATUSEHAT, it is hoped that the results of this study can follow the government's success in significantly reducing the rate of pulmonary TB. The method used is the Design Thinking (DT) Framework. DT is a consumer-centric approach. User-centric UI/UX designs will have a higher acceptance rate. DT has been successfully applied in various fields such as healthcare, education, marketing, sales, management and so on. DT includes 5 phases, namely: 1) Empathize, 2) Define, 3) Ideate, 4) Prototype, and 5) Test. The result of the study was a UI/UX design evaluated by the SUS (System Usability Scale) method which achieved an average score of 82.5. The interpretation of the number shows that the UI/UX design is acceptable to respondents with category A (very good).